Glass composition, glass fiber, and electronic product

By designing a new glass composition and combining a specific composition proportional relationship, the problem of crystal phenomena in glass fibers during production is solved, and the low thermal expansion coefficient, low dielectric constant and low dielectric loss of glass fibers are achieved. It is used in electronic products, improving the transmission efficiency and resistance to temperature deformation.

JP2025058828AActive Publication Date: 2025-04-09FULLTECH FIBER GLASS CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024012594
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-28
Filing Date
2024-01-31
Publication Date
2025-04-09
Estimated Expiration
2044-01-31

AI Technical Summary

Technical Problem

Existing glass fiber materials are prone to crystallization during the production process, resulting in unsmooth fiber-spinning process, affecting the quality and performance of glass fibers. Especially when low thermal expansion coefficient, low dielectric constant and low dielectric loss are required in electronic products, it is difficult to avoid deformation caused by temperature changes.

Method used

By designing a new glass composition, the total content is 100 wt%, where the SiO2 content is between 45 wt% and 61 wt%, the Al2O3 content is between 15 wt% and 22 wt%, the CaO, MgO, ZnO, CuO and B2O3 content is within a specific range, and through a specific composition proportional relationship (such as Equation 1: x=(C+M)/A+(C+M)/B, 0.3≤x≤1.5), it ensures that the glass composition has a low thermal expansion coefficient, a low dielectric constant, and a good rotational processing performance.

Benefits of technology

The glass composition is composed of low thermal expansion coefficient, low dielectric constant and low dielectric loss, and has good rotation processing performance, thereby producing glass fibers with low thermal expansion coefficient, low dielectric constant and low dielectric loss, which are used in electronic products, improving the transmission efficiency and temperature deformation resistance of electronic products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025058828000001
    Figure 2025058828000001
  • Figure 2025058828000002
    Figure 2025058828000002
Patent Text Reader

Abstract

To provide a glass composition having low coefficient of thermal expansion, low dielectric constant, low dielectric loss tangent, and good spinning processability.SOLUTION: A glass composition includes, based on 100 wt. % of the glass composition, SiO2 present in an amount ranging from 45 wt.% to 61 wt.%; Al2O3 present in an amount ranging from 15 wt. % to 22 wt.%; CaO present in an amount ranging from 0.1 wt.% to 6 wt.%; MgO present in an amount of more than 0 wt. % and less than 2 wt.%; ZnO present in an amount of more than 0 wt.% and less than 8 wt.%; CuO present in an amount of more than 0 wt.% and less than 7 wt.%; and B2O3 present in an amount of more than 6 wt.% and less than 18 wt.%, wherein the amount of CaO, the amount of MgO, the amount of Al2O3, and the amount of B2O3 satisfy the following Equation (1): x=(C+M) / A+(C+M) / B, where x ranges from 0.3 to 1.5, C represents the amount of CaO, M represents the amount of MgO, A represents the amount of Al2O3, and B represents the amount of B2O3.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a glass composition, a glass fiber, and an electronic product, and more particularly to a glass composition having a low thermal expansion coefficient, a low dielectric constant and a low dielectric loss tangent, and spinning processability, a glass fiber including the glass composition, and an electronic product including the glass fiber. [Background technology]

[0002] Today's electronic products require high transfer speeds, but at the same time, it is necessary to overcome the adverse effects on electronic products of residual stress caused by thermal expansion during operation.

[0003] Therefore, the glass fiber cloth used as a reinforcing material in a printed circuit board must have not only a low dielectric constant and a low dielectric loss tangent to meet high transfer speeds, but also a low thermal expansion coefficient to prevent electronic products from deforming due to temperature changes.

[0004] Fiberglass fabrics are produced by weaving or knitting fiberglass yarns, the fiberglass yarns being formed from glass fibers, which in turn are produced by melting and spinning a glass composition.

[0005] If crystallization occurs in the glass composition during the process of producing glass fibers, the spinning process of producing glass fibers from the glass composition will be sluggish, which will result in poor quality of the obtained glass fibers and adversely affect the properties of the glass fibers.

[0006] Patent Document 1 discloses a low dielectric glass composition. The low dielectric glass composition contains SiO2 in the range of more than 49 wt% and not more than 53 wt%, Al2O3 in the range of 13 wt% to 17 wt%, B2O3 in the range of 18 wt% to 24 wt%, MgO in the range of more than 2 wt% and not more than 4.5 wt%, CaO in the range of more than 2 wt% and not more than 5 wt%, TiO2 in the range of more than 0.6 wt% and less than 3.5 wt%, and CaO in the range of more than 0 wt% and not more than 0.6 wt%. % to 0.6 wt%, and the total content of MgO+CaO+ZnO is greater than 8 wt% and less than 11 wt%. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Taiwan Patent No. 725930 Summary of the Invention [Problem to be solved by the invention]

[0008] The object of the present invention is to provide a new glass composition having a low thermal expansion coefficient, a low dielectric constant, a low dielectric tangent and good spinnability, a glass fiber having a low thermal expansion coefficient, a low dielectric constant and a low dielectric tangent, and an electronic product having good transfer efficiency and being resistant to deformation due to temperature changes. [Means for solving the problem]

[0009] In order to achieve the above object, the present invention provides a composition comprising: SiO2 with a content in the range of 45wt% to 61wt%; Al2O3 with a content in the range of 15wt% to 22wt%; CaO with a content in the range of 0.1wt% to 6wt%; MgO having a content of more than 0 wt% and less than 2 wt%, ZnO having a content of more than 0 wt% and less than 8 wt%, CuO having a content of more than 0 wt% and less than 7 wt%, B2O3, the content of which is in the range of more than 6 wt% and less than 18 wt%, The CaO content, the MgO content, the Al2O3 content, and the B2O3 content have a relationship that satisfies the following formula 1: Equation 1: x=(C+M) / A+(C+M) / B, In the formula, the value of x is in the range of 0.3 to 1.5. C represents the CaO content, M represents the content of MgO, A represents the content of Al2O3, The present invention provides a glass composition, wherein B represents the content of B2O3.

[0010] The present invention also provides a glass fiber comprising the above glass composition.

[0011] The present invention also provides an electronic product comprising the above-mentioned glass fiber. Effect of the Invention

[0012] The glass composition of the present invention has a low thermal expansion coefficient, a low dielectric constant, a low dielectric loss tangent, and good spinnability, by designing the combination of each of the above components and the range of the content of each component, particularly the MgO content being in the range of more than 0wt% and less than 2wt%, and the CaO content, the MgO content, the Al2O3 content, and the B2O3 content satisfying formula 1 (i.e., the value of x is in the range of 0.3 to 1.5). In addition, since the glass composition of the present invention has good spinnability, the glass fiber of the present invention obtained from the glass composition also has a low thermal expansion coefficient, a low dielectric constant, and a low dielectric loss tangent, and thus the electronic product of the present invention containing the glass fiber has the advantages of good transfer efficiency and being less likely to deform due to temperature changes. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention will now be described.

[0014] [Glass composition] The glass composition of the present invention contains, with a total amount being 100 wt%, SiO2 (silicon dioxide) with a content ranging from 45 wt% to 61 wt%, Al2O3 (aluminum oxide) with a content ranging from 15 wt% to 22 wt%, CaO (calcium oxide) with a content ranging from 0.1 wt% to 6 wt%, MgO (magnesium oxide) with a content ranging from more than 0 wt% to less than 2 wt%, ZnO (zinc oxide) with a content ranging from more than 0 wt% to less than 8 wt%, CuO (copper oxide) with a content ranging from more than 0 wt% to less than 7 wt%, and B2O3 (boron oxide) with a content ranging from more than 6 wt% to less than 18 wt%.

[0015] In addition, the inventors of the present invention conducted research, testing, analysis and induction on the glass composition, and as a result, designed the CaO content, the MgO content, the Al2O3 content and the B2O3 content to satisfy the following formula 1.

[0016] Equation 1: x=(C+M) / A+(C+M) / B, In the formula, the value of x is in the range of 0.3 to 1.5. C represents the CaO content, M represents the content of MgO, A represents the content of Al2O3, B represents the content of B2O3.

[0017] By combining the design of Formula 1 and the range of the value of x with the specific content range of each component in the glass composition of the present invention, particularly the content of MgO being in the range of more than 0 wt % and less than 2 wt %, the glass composition of the present invention has a low thermal expansion coefficient, a low dielectric constant, a low dielectric loss tangent, and good spinnability.

[0018] The effect of each component and its content range in the present invention will be described below.

[0019] SiO2 is a main component of the glass composition of the present invention. Since the content of SiO2 in the glass composition is within the range of 45 wt% to 61 wt%, the viscosity of the glass composition can be reduced, which is advantageous for melting the glass composition.

[0020] Since the content of Al2O3 in the glass composition is within the range of 15 wt% to 22 wt%, the viscosity of the glass composition can be reduced, which is advantageous for melting the glass composition, and crystallization is less likely to occur in the glass composition during the process of producing glass fibers, resulting in good spinnability.

[0021] Since the CaO content in the glass composition is within the range of 0.1 wt% to 6 wt%, the viscosity of the glass composition can be reduced, which is advantageous for melting the glass composition; in addition, crystallization is less likely to occur in the glass composition during the process of producing glass fibers, good spinning processability can be obtained, and the low thermal expansion coefficient of the glass composition can be reduced.

[0022] Since the content of MgO in the glass composition is within the range of more than 0 wt% and less than 2 wt%, the viscosity of the glass composition can be reduced, which is advantageous for melting the glass composition, and the structure of the glass composition can be made tighter, so that the glass composition and the glass fibers produced from the glass composition have the advantages of having a low thermal expansion coefficient and a low dielectric constant.

[0023] Since the content of ZnO in the glass composition is in the range of more than 0 wt % and less than 8 wt %, the thermal expansion coefficient of the glass composition and the thermal expansion coefficient of the glass fiber produced from the glass composition can be reduced.

[0024] Since the CuO content in the glass composition is within the range of more than 0 wt % and less than 7 wt %, the structure of the glass composition can be made dense, the thermal expansion coefficient of the glass composition and the thermal expansion coefficient of the glass fiber produced from the glass composition can be reduced, and crystallization is less likely to occur in the glass composition during the process of producing the glass fiber, resulting in good spinnability.

[0025] Since the content of B2O3 in the glass composition is within the range of more than 6 wt% and less than 18 wt%, the viscosity of the glass composition can be reduced, which is favorable for the melting of the glass composition; in addition, crystallization is unlikely to occur in the glass composition during the process of producing glass fiber, good spinning processability can be obtained, and the structure of the glass composition can be made tight. Thus, the glass composition and the glass fiber produced from the glass composition have the advantages of a low thermal expansion coefficient, a low dielectric constant, and a low dielectric tangent.

[0026] In some embodiments of the present invention, the glass composition further contains F2 (fluorine) in a content range of more than 0 wt% and not more than 1 wt%, where the total amount is 100 wt%. Even when F2 is further contained, the CaO content, the MgO content, the Al2O3 content, and the B2O3 content also satisfy formula 1.

[0027] In addition, the CaO content, the MgO content, the Al2O3 content, the B2O3 content, and the F2 content are designed to satisfy the relationship of the following formula 2.

[0028] Equation 2: y = (C + M) / A + (C + M) / (B + F), In the formula, the value of y is in the range of 0.3 to 1.5. C represents the CaO content, M represents the content of MgO, A represents the content of Al2O3, B represents the content of B2O3, F represents the content of F2.

[0029] Since the content of F2 in the glass composition is within the range of more than 0 wt % and not more than 1 wt %, the viscosity of the glass composition can be reduced, which is advantageous for melting the glass composition, and there is also an advantage in that a lower dielectric constant and a lower dielectric tangent can be imparted to the glass composition.

[0030] In some embodiments of the present invention, the glass composition of the present invention may further include other substances. The other substances are impurities in each component of the glass composition. In some embodiments of the present invention, the glass composition includes the other substances in an amount of 1.2 wt% or less, based on a total amount of 100 wt%.

[0031] In some embodiments of the invention, the other substances include Na2O (sodium oxide), K2O (potassium oxide), Fe2O3 (iron oxide), TiO2 (titanium dioxide), or combinations thereof.

[0032] In some embodiments of the present invention, the glass composition has a coefficient of thermal expansion of 2.8 ppm / ° C. or less, a dielectric constant of 4.9 or less and a dissipation factor of 0.0035 or less at a frequency of 10 GHz, and a forming window for spinning the glass composition is greater than 100° C.

[0033] Since the spinning window of the glass composition exceeds 100° C., it is advantageous for the spinning operation when producing glass fibers from the glass composition.

[0034] [Glass fiber] The glass fiber of the present invention comprises the above-described glass composition.

[0035] The method for producing the glass fiber of the present invention includes, for example, melting the glass composition of the present invention to obtain a glass liquid, and then subjecting the glass liquid to a spinning process to obtain the glass fiber, but is not limited thereto.

[0036] The parameters and specific steps for producing glass fibers are well known in the relevant fields. Therefore, the parameters for producing glass fibers vary depending on the content of each component in the glass composition, but the adjustment of the parameters for producing glass fibers is well known to those skilled in the art, so a detailed description is omitted here.

[0037] Since the glass composition of the present invention has advantages such as a low thermal expansion coefficient, a low dielectric constant, a low dielectric tangent, and good spinnability, the glass fiber of the present invention produced from the glass composition also has a low thermal expansion coefficient, a low dielectric constant, and a low dielectric tangent.

[0038] In some embodiments of the invention, the glass fiber has a coefficient of thermal expansion of 2.8 ppm / ° C. or less, and the glass fiber has a dielectric constant of 4.9 or less and a dissipation factor of 0.0035 or less at a frequency of 10 GHz.

[0039] [Electronic products] The electronic product of the present invention includes the glass fiber described above.

[0040] Since the glass fiber of the present invention has a low thermal expansion coefficient, a low dielectric constant, and a low dielectric tangent, the electronic products of the present invention that are constructed using the glass fiber and contain the glass fiber have the advantages of good transfer efficiency and being less likely to deform due to temperature changes.

[0041] The type of electronic product of the present invention is not particularly limited, and all electronic products containing the glass fiber of the present invention are included in the embodiments of the electronic product of the present invention.

[0042] In some embodiments of the present invention, the electronic product is a printed circuit board.

[0043] In some embodiments of the present invention, the electronic product is an integrated circuit board.

[0044] In some embodiments of the present invention, the electronic product is a radar dome.

[0045] Examples of the present invention will now be described, with the understanding that these examples are illustrative and explanatory and should not be construed as limiting the present invention.

[0046] <Example 1> A glass composition was obtained by mixing SiO2, Al2O3, CaO, MgO, ZnO, CuO, B2O3 and F2.

[0047] The glass composition contains, with the total amount of the glass composition being 100 wt%, 55.4 wt% SiO2, 18.0 wt% Al2O3, 2.3 wt% CaO, 1.9 wt% MgO, 7.0 wt% ZnO, 0.2 wt% CuO, 14.0 wt% B2O3, 0.7 wt% F2, and 0.5 wt% other substances (impurities contained in the above components, including Na2O, K2O, and Fe2O3), and the value of x in the above formula 1 is 0.54 and the value of y in the above formula 2 is 0.52. <Examples 2 to 7 and Comparative Examples 1 to 3> The manufacturing methods of Examples 2 to 7 and Comparative Examples 1 to 3 were the same as those of Example 1, except for the content of each component. The content of each component of Examples 2 to 7 and Comparative Examples 1 to 3 is shown in Tables 1 and 2.

[0048] Other substances contained in the glass compositions of Examples 2 to 7 include Na2O, K2O, and Fe2O3, and other substances contained in the glass compositions of Comparative Examples 1 to 3 include Na2O, K2O, Fe2O3, and TiO2.

[0049] [Evaluation items] The following evaluations were performed on the glass compositions of Examples 1 to 7 and Comparative Examples 1 to 3. For ease of explanation, the evaluation methods for the following evaluation items will be described using the glass composition of Example 1 as a representative, and the other Examples and Comparative Examples were performed using the same evaluation methods. The evaluation results are shown in Tables 1 and 2.

[0050] <Measurement of coefficient of thermal expansion (abbreviation: CTE, unit: ppm / ℃)> The glass composition of Example 1 was placed in a high-temperature furnace and heated at a temperature of 1500°C to 1600°C for 1 to 4 hours to obtain a completely melted liquid glass. The liquid glass was then poured into a graphite crucible having a diameter of 40 mm, and the graphite crucible was placed in an annealing furnace preheated to 800°C, and the liquid glass was cooled to room temperature (25°C) to form a glass block.

[0051] The glass block was cut and polished to obtain a sample having a size of 0.5 cm×0.5 cm×2 cm.

[0052] Then, using a thermomechanical analyzer (Hitachi, model number: TMA71000), the sample was heated at a heating rate of 10° C. / min, the length of the sample was measured at 50° C. and 200° C., and the amount of change in length and the amount of change in temperature were calculated from the measured length and temperature, and then the thermal expansion coefficient of the glass composition of Example 1 was calculated. The results are shown in Tables 1 and 2.

[0053] <Measurement of dielectric constant (abbreviation: Dk) and dielectric loss tangent (abbreviation: Df)> The glass composition of Example 1 was placed in a high-temperature furnace and heated at a temperature of 1500°C to 1600°C for 1 to 4 hours to obtain a completely melted liquid glass. The liquid glass was then poured into a graphite crucible having a diameter of 40 mm, and the graphite crucible was placed in an annealing furnace preheated to 800°C, and the liquid glass was cooled to room temperature (25°C) to form a glass block.

[0054] The glass block was polished to prepare a glass sheet having a thickness of 0.60 mm to 0.79 mm. The dielectric constant and dielectric loss tangent of the glass sheet at a frequency of 10 GHz were measured using a vector network analyzer (ZNB20, manufactured by R&S, Germany) in combination with a split post dielectric resonator (manufactured by WAVERAY TECHNOLOGY CO., LTD., Taiwan), to obtain the dielectric constant and dielectric loss tangent of the glass composition of Example 1.

[0055] <Measurement of spinning window (abbreviation: ΔT, unit: °C)> The glass composition of Example 1 was placed in a high-temperature furnace and heated at a temperature of 1500°C to 1600°C for 1 to 4 hours to obtain a completely melted liquid glass. The liquid glass was then poured into a graphite crucible having a diameter of 40 mm, and the graphite crucible was placed in an annealing furnace preheated to 800°C, and the liquid glass was cooled to room temperature (25°C) to form a glass block.

[0056] 2.25g of the glass block was taken and placed in a high-temperature furnace, then heated to a specific temperature and maintained at that temperature for 2 hours, and the glass block was then removed from the high-temperature furnace and cooled to room temperature (25°C) by standing, and the presence or absence of crystals in the glass block was observed. If crystals were present, the specific temperature was the devitrification temperature of the glass composition of Example 1. The forming window for spinning the glass composition of Example 1 was obtained by subtracting the devitrification temperature from the temperature at which the glass composition of Example 1 had a viscosity of 1000 poise.

[0057] The above glass blocks and glass sheets can both be considered as glass compositions.

[0058] [Table 1]

[0059] [Table 2]

[0060] As shown in Tables 1 and 2, the glass composition of Comparative Example 1 has an x ​​value of less than 0.3, so the spinning window is less than 50°C, which is disadvantageous for the spinning process when producing glass fibers, and the glass composition of Comparative Example 2 has an x ​​value of more than 1.5, so the dielectric constant and dielectric loss tangent at a frequency of 10 GHz are high. Compared to the glass compositions of Comparative Example 1 and Comparative Example 2, the glass compositions of Examples 1 to 7 satisfy the above formula 1 (i.e., the x value is within the range of 0.3 to 1.5), so they are superior in thermal expansion coefficient, dielectric constant and dielectric loss tangent at a frequency of 10 GHz, and spinning window.

[0061] The glass composition of Comparative Example 3 has a high dielectric constant and dielectric loss tangent at a frequency of 10 GHz because the MgO content is 2 wt% or more. In comparison with the glass composition of Comparative Example 3, the glass compositions of Examples 1 to 7 have a MgO content in the range of more than 0 wt% and less than 2 wt%, and therefore have better thermal expansion coefficients, dielectric constants and dielectric loss tangents at a frequency of 10 GHz, and spinning window.

[0062] According to the above, the glass compositions of Examples 1 to 7 contain, with the total amount of the glass composition being 100 wt%, SiO2 with a content in the range of 45 wt% to 61 wt%, Al2O3 with a content in the range of 15 wt% to 22 wt%, CaO with a content in the range of 0.1 wt% to 6 wt%, MgO with a content in the range of more than 0 wt% and less than 2 wt%, ZnO with a content in the range of more than 0 wt% and less than 8 wt%, CuO with a content in the range of more than 0 wt% and less than 7 wt%, , and B2O3 with a content in the range of more than 6wt% and less than 18wt%, and the CaO content, MgO content, Al2O3 content and B2O3 content all satisfy the above formula 1 (i.e., the value of x is in the range of 0.3 to 1.5), so that the glass compositions of Examples 1 to 7 have a thermal expansion coefficient of 2.8ppm / °C or less, a dielectric constant of 4.9 or less at a frequency of 10GHz, a dielectric loss tangent of 0.0035 or less, and a spinning window of more than 100°C. Therefore, it has been proven that the glass composition of the present invention has a low thermal expansion coefficient, a low dielectric constant, a low dielectric loss tangent and good spinning processability.

[0063] Therefore, by designing the combination of the above components and the ranges of the contents of each of the components in the glass composition of the present invention, in particular by designing the MgO content to be within the range of more than 0 wt% and less than 2 wt%, and the CaO content, the MgO content, the Al2O3 content and the B2O3 content to satisfy formula 1 (i.e., the value of x is within the range of 0.3 to 1.5), the glass composition of the present invention has a low thermal expansion coefficient, a low dielectric constant, a low dielectric tangent and good spinnability, thereby achieving the objects of the present invention.

[0064] In addition, since the glass composition of the present invention has good spinnability, the glass fiber of the present invention obtained from the glass composition also has a low thermal expansion coefficient, a low dielectric constant and a low dielectric tangent, and thus the electronic product of the present invention containing the glass fiber has the advantages of good transfer efficiency and being less likely to deform due to temperature changes.

[0065] The above embodiment is illustratively intended to explain the principles and effects of the present invention, and is not intended to limit the present invention. Those skilled in the art may make some changes or modifications to the above embodiment without departing from the spirit and scope of the present invention. Therefore, all changes and modifications made by those skilled in the art without departing from the gist of the present invention should be considered to be within the scope of protection of the present invention. [Industrial Applicability]

[0066] The present invention is suitable for providing a glass composition having a low thermal expansion coefficient, a low dielectric constant, a low dielectric loss tangent and good spinnability.

Claims

1. The total amount is 100 wt%. SiO content is within the range of 45 wt% to 61 wt% 2 and, Al content in the range of 15wt% to 22wt% 2 O 3 and, CaO having a content in the range of 0.1 wt% to 6 wt%; MgO having a content of more than 0 wt% and less than 2 wt%; ZnO having a content of more than 0 wt% and less than 8 wt%, CuO having a content of more than 0 wt % and less than 7 wt %; B content is in the range of more than 6 wt% and less than 18 wt% 2 O 3 and CaO content, MgO content, Al 2 O 3 Content of and B 2 O 3 The content of satisfies the following formula 1, Formula 1: x=(C+M) / A+(C+M) / B, wherein the value of x is in the range of 0.3 to 1.5; C represents the CaO content, M represents the content of MgO, A is Al 2 O 3 represents the content of B is B 2 O 3 The glass composition according to claim 1, wherein the content of

2. F content is in the range of more than 0 wt% and 1 wt% or less, with the total amount being 100 wt%. 2 The glass composition of claim 1 further comprising:

3. CaO content, MgO content, Al 2 O 3 Content of B 2 O 3 Content of and F 2 The content of satisfies the following formula 2, Formula 2: y=(C+M) / A+(C+M) / (B+F), wherein the value of y is in the range of 0.3 to 1.5; C represents the CaO content, M represents the content of MgO, A is Al 2 O 3 represents the content of B is B 2 O 3 represents the content of F is F 2 The glass composition according to claim 2, characterized in that the content of

4. A glass fiber comprising the glass composition according to any one of claims 1 to 3.

5. An electronic product comprising the glass fiber of claim 4.

6. 6. The electronic product of claim 5, which is a printed circuit board.

7. 6. The electronic product of claim 5, which is an integrated circuit board.

8. 6. The electronic product of claim 5, which is a radar dome.

Citation Information

Patent Citations

  • Alkali aluminosilicate glass for 3D precision molding and thermal bending.

    JP2013528561A

  • Glass powder for three-dimensional molding

    JP2018048057A

  • Glass composition, glass fiber, and product including the same

    JP2023038176A

  • Glass composition for glass fibers, glass fiber, and glass fiber-reinforced resin molded article

    WO2023276619A1

  • TW725930